Biomechanical comparison of different fixation methods in metatarsal shaft fractures: A cadaver study. (February 2022) - Trost, Matthias; Knieps, Matthias; Hackl, Michael; Frey, Sönke; Scaal, Martin; Müller, Lars Peter; Dargel, Jens; Gick, Sascha
Abstract: Background: Various fixation methods are available for the operative treatment of metatarsal shaft fractures: Kirschner wire, Titanium elastic nail, plate, or an intramedullary bone stabilization system within a balloon catheter. The aim of this study was to compare the stability of these techniques. Methods: 72 metatarsals II to V from fresh frozen human cadaver feet were used. A shaft fracture was performed and fixed with a 1.6-mm Kirschner wire, a 1.5-mm Titanium elastic nail, a locking 6-hole-plate, or an intramedullary bone stabilization system. In a cantilever configuration, the head of the metatarsals was loaded statically (2 mm/min until failure; all groups) or cyclically (0 to 20 N for 1000 cycles with 10 mm/s, after 1000 cycles 2 mm/min until failure; plate and bone stabilization system). Findings: The mean failure strength for static loading was 17 N for Kirschner wire, 13 N for Titanium elastic nail, 73 N for plate and 34 N for the bone stabilization system ( P  < .01). For cyclic loading, the mean cycle of failure was 1000 for plate and 961 for the bone stabilization system ( P  = .76). The mean failure strength after cyclic loading was 73 N for plate and 48 N for the bone stabilization system ( P  = .03). Interpretation: Stability differs depending on the fixation method, with a plate showing the greatest stability and Kirschner wire or Titanium elastic nail the least. The stability of the bone stabilization system for fixing metatarsal shaft fractures is intermediate. Highlights: Stability differs depending on the fixation method of metatarsal shaft fractures. A plate is showing the greatest stability and Kirschner wire or Titanium elastic nail the least. The stability of the bone stabilization system is intermediate.